Consolidating passenger and freight transportation in an urban–rural transit system - Tao Wang; Hongzhang Shao; Xiaobo Qu; Jonas Eliasson (Fundamental Research)
Buses are the most critical part of urban–rural transit systems. However, bus transit services in urban–rural areas face a trade-off between the need for better services and the low profitability resulting from low travel demand. In this study, we show that we can improve the utilization and profitability of urban–rural buses by merging freight transportation with passenger transportation. We developed a mixed-integer program to model and analyze the coordination between freight and passenger transportation in an urban–rural transit system. We then conducted a case study to evaluate the effectiveness of the proposed approach. The numerical results indicate that the consolidation of passenger and freight transportation significantly reduces the operation cost of logistics companies and improves the profit of bus companies. We finally discuss the consolidation’s positive impacts on logistics companies, bus service providers, and society.